EXPRESSION ANALYSIS OF PHOSPHATASE REGENERATING LIVER-3 (PRL-3) IN OVARIAN CARCINOMA - Rina Masadah; Risma Maharani; Syahrul Rauf (Nusantara Medical Science Journal, 2016)
ABSTRACT Introduction: Ovarian carcinoma is the fifth most caused of gynecological death and its incidence has been shaply increased in the last five years. Phosphatase Regenerating Liver-3 (PRL-3) is a protein that play an important role in malignant cell proliferation, differentiation, and motilily. Methods: This study analized PRL-3 protein expression in paraffin block of ovarian carcinoma tissue sections by immunohistochemical analysis using PRl-3 monoclonal antibody. Results: We found that PRL-3 was expressed in all tissues analized. However, statistical testing did not found any relation between PRL-3 expression and clinical stages, also no relation found between PRL-3 expression and histological differentiation degree of ovarian carcinoma. Conclusion: No relation found between PRL-3 expression in early stage and advance stage of ovarian carcinoma, as well as among various degree of histological differentiation. Study using more variable obviously needed to gain the knowledge about the role of PRL-3 in ovarian carcinoma pathogenesis. Keywords: Ovarian carcinoma, Phosphatase Regenerating Liver-3